The Effectiveness of Group Guidance Services with Symbolic Modeling Techniques to Increase Empathy of Santri at Ma'had Al-Khoirot MAN 2 Jember - Rahmah, Unzilatur; Maghfiroh, Nasruliyah Hikmatul; Rahmawati, Weni Kurnia (Konseling Edukasi : Journal of Guidance and Counseling, 2024)
The Effectiveness of Group Guidance Services with Symbolic Modeling Techniques to Increase Empathy of Santri at Ma'had Al-Khoirot MAN 2 Jember. The study examined the effectiveness of group guidance services using symbolic modeling techniques to foster empathy in santri of Al-Khoirot Islamic Boarding School MAN 2 Jember. This study is important because it offers an innovative approach to improving empathy in students through group guidance with symbolic modeling techniques. The research approach uses a quantitative method with a pre-experimental design methodology of the one group pretest-posttest type. The data collection method used was the Wilcoxon Test. The population of the study was santri of Al-Khoirot Islamic Boarding School MAN 2 Jember with a total of 39 students, with a sample of 6 students. The results of this study indicate that group guidance services using symbolic modeling techniques are effective in improving empathy in santri of Al-Khoirot Islamic Boarding School MAN 2 Jember. Before being given treatment, the level of empathy in students had an average of 229.5, but after being given treatment and posttest 4 times, there was a significant increase of 282.5. Analysis using the Wilcoxon test produced an Asymp value. Sig. (2-tailed) of 0.028, shows a significant influence between pretest and post-test, so that the research hypothesis can be accepted. The conclusion is that the symbolic modeling method is able to foster empathy in santri of Al-Khoirot Islamic Boarding School MAN 2 Jember, so that this therapy can be used as an alternative guidance strategy for developing empathy characters in Islamic boarding schools.Keywords: Group Guidance, Symbolic Modeling Techniques, Empathy Santri